2015
DOI: 10.3168/jds.2014-8728
|View full text |Cite
|
Sign up to set email alerts
|

Milk fatty acids as possible biomarkers to diagnose hyperketonemia in early lactation

Abstract: The aim of this study was to assess the potential of milk fatty acids as diagnostic tool for hyperketonemia of 93 dairy cows in a 3×2 factorial arrangement. Cows were fed a glucogenic or lipogenic diet and originally were intended to be subjected to a 0-, 30-, or 60-d dry period. Nevertheless, some of the cows, which were intended for inclusion in the 0-d dry period group, dried off spontaneously. Milk was collected in wk 2, 3, 4, and 8 of lactation for milk fat analysis. Blood was sampled from wk 2 to 8 after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…A larger data set using 92 early-lactation Holstein-Friesian cows from a research herd in the Netherlands found a 50% increased risk of plasma NEFA ≥0.6 mmol/L in cows with at least 240 g/kg of C18:1 cis-9 in milk fat; however, sensitivity for this method was just under 50% (Jorjong et al, 2014). This group also reported that a milk fat ratio of C18:1 cis-9 to C15:0 >40 was present in 70% of hyperketonemic animals (Jorjong et al, 2015). Mann et al (2016) investigated the diagnostic value of milk fatty acids and fatty acid ratios for correct classification of 84 multiparous cows in a research herd in New York State as having high NEFA or BHB concentrations.…”
Section: Milkmentioning
confidence: 97%
See 1 more Smart Citation
“…A larger data set using 92 early-lactation Holstein-Friesian cows from a research herd in the Netherlands found a 50% increased risk of plasma NEFA ≥0.6 mmol/L in cows with at least 240 g/kg of C18:1 cis-9 in milk fat; however, sensitivity for this method was just under 50% (Jorjong et al, 2014). This group also reported that a milk fat ratio of C18:1 cis-9 to C15:0 >40 was present in 70% of hyperketonemic animals (Jorjong et al, 2015). Mann et al (2016) investigated the diagnostic value of milk fatty acids and fatty acid ratios for correct classification of 84 multiparous cows in a research herd in New York State as having high NEFA or BHB concentrations.…”
Section: Milkmentioning
confidence: 97%
“…They found that although several fatty acid concentrations were associated with elevated NEFA and BHB, correct classification was only moderate; thus, they could not recommend this measurement method over direct blood detection methods. Both Jorjong et al (2014Jorjong et al ( , 2015 and Mann et al (2016) stated that practical use of this information most likely requires routine analysis of milk fatty acids and repeated sampling of an individual animal; however, current technology does not support a method of on-farm milk fatty acid determination that is rapid and cost effective.…”
Section: Milkmentioning
confidence: 99%
“…Many studies have found that BHBA is a predominant and stable blood ketone body in ruminant ketosis [4,10], which, therefore, has been widely used for clinically diagnosing and classifying ketosis in dairy cows [11]. Furthermore, a large number of molecular biomarkers have been also identified to be associated with ketosis, such as milk fatty acids [12], serum hepatokines [13], inflammatory biomarkers [14], methylglyoxal [2], metabolites [15], mineral elements [16], protein profiling [17], and amino acids [18] in blood.…”
Section: Introductionmentioning
confidence: 99%
“…Higher vaccenic acids in OP and SH diets seems to be positively correlated with negative energy balances in goats. Jorjong et al (2015) found positive correlation between negative energy balance and oleic acid in dairy cow.…”
Section: Milk Production and Fatty Acidsmentioning
confidence: 80%
“…Excessive amounts of NEFA released during body fat mobilization are transferred to the milk. The major NEFA released are palmitic acid, stearic acid and oleic acid, and their elevated concentration in milk fat of those FA were identified as valuable early warning biomarkers for negative energy balance (Jorjong et al, 2015). Greater (P < 0.05) concentration of palmitic acid, heptadecanoic acid and vaccenic acid were found in OP and SH than BRL, and the highest value of oleic acid was found in SH diet.…”
Section: Metabolites In Milk Urine and Plasmamentioning
confidence: 99%